Institutions authorized to prevent and combat phenomenon of corruption in Poland - Kułak, Izabela (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Corruption is a threat to people, society, the state and the economy. It is a phenomenon that particularly harms the basic principles of the functioning of the country. This article focuses on entities authorized to prevent corruption. Individual bodies, services and institutions obliged to fight corruption and equipped with a number of competences that facilitate the performance of their tasks are discussed. The Central Anticorruption Bureau, the Internal Security Agency, the Police, the Public Prosecutor’s Office and other entities forming the system of prevention and combating corruption crime in Poland are presented. To discuss the subject it is necessary to refer to legal acts and the literature. The aim of this description, however, is not a comprehensive presentation of the subject matter indicated in the title, as it seems impossible to provide an exhaustive study of each entity authorized to prevent corruption in only one article. Due to the limited scope of the article only a synthetic presentation of the subject matter has been presented.

Korupcja stanowi niebezpieczeństwo dla człowieka, społeczeństwa, państwa, gospodarki. Jest zjawiskiem, które w sposób szczególny godzi w podstawowe zasady funkcjonowania kraju. Przedmiotem rozważań podjętych w niniejszym artykule są podmioty uprawnione do zapobiegania korupcji. Omówiono poszczególne organy, służby i instytucje zobowiązane do walki z procederem korupcji i wyposażone w szereg kompetencji ułatwiających realizowanie nałożonych na nie zadań. Przedstawione zostały Centralne Biuro Antykorupcyjne, Agencja Bezpieczeństwa Wewnętrznego, Policja, Prokuratura i inne podmioty stanowiące część systemu zapobiegania i zwalczania przestępczości korupcyjnej w Polsce. Dla omówienia poruszanego tematu obligatoryjne jest odniesienie się do aktów prawnych oraz korzystanie z literatury. Celem niniejszego opracowania nie jest jednak kompleksowe przedstawienie wskazanej w tytule tematyki, gdyż niemożliwe wydaje się dokonanie rzetelnego opisu każdego z podmiotów uprawnionych do zapobiegania korupcji tylko w jednym artykule. Artykuł ze względu na ograniczone ramy zawiera jedynie syntetyczne przedstawienie tytułowej problematyki.
Keywords: corruption; corruption prevention; anti-corruption activities; institutions in the fight against corruption; korupcja; zapobieganie korupcji; działania antykorupcyjne; podmioty w walce z korupcją